Where ichthyofaunal provinces meet: the fish fauna of the Lake Edward system, East Africa. Issue 5 (29th May 2019) - Decru, Eva; Vranken, Nathan; Bragança, Pedro H. N.; Snoeks, Jos; Van Steenberge, Maarten
Abstract: Based on literature, museum collections and three recent expeditions, an annotated species list of the Lake Edward, East Africa, drainage system is presented, excluding the endemic haplochromines. A total of 34 non‐ Haplochromis species belonging to 10 families and 21 genera are recorded from the system. Three of these are endemic and two others have been introduced in the region. Six species are new records for the Lake Edward system. A species accumulation curve indicates that we probably covered most of the non‐ Haplochromis species in the area sampled during the recent expeditions, but undetected species might still be present in the Congolese part of the system, which is poorly sampled. A comparison of the species list with those of neighbouring basins confirmed the placement of the Lake Edward system within the east‐coast ichthyofaunal province.